USE OF GLUE VALUE AT RISK FOR OPTIMAL PORTFOLIO RISK MEASUREMENT WITH THE SINGLE INDEX MODEL METHOD - Turnika Afdatul Rafni; Dina Agustina (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
Creating an optimal portfolio and measuring risk are ways that can be used to reduce losses and maximize returns in an investment. In this study, the optimal portfolio is formed using the Single Index Model method, which assumes stock returns are influenced only by market returns. The stocks used are stocks that are consistently included in the IDX30 index during the period October 24, 2022-October 25, 2024 and provide positive expected returns, so that based on the Single Index Model method, 5 stocks are included in the optimal portfolio with the proportion of each stock as follows, PT Indofood Sukses Makmur Tbk (INDF) 30%, PT Barito Pacific Tbk (BRPT) 8%, PT Bank Mandiri Tbk (BMRI) 35%, PT Bank Central Asia Tbk (BBCA)17%, and PT Bank Negara Indonesia Tbk (BBNI) 10%. The risk of the optimal portfolio can be calculated using the Glue Value at Risk method, which provides a more accurate and coherent measure of risk. In this study with a confidence level of and and used a high distortion function and , the Glue Value at Risk amount for the optimal portfolio was obtained at Rp1,996,926. The backtesting results show that Glue Value at Risk provides valid and accurate results for measuring risk at this level of confidence.